Bacteria-Metal Interactions - Saffarini, Daad (Springer, 2015)
This book provides a detailed description and analysis of the reduction and metabolism of metals and metalloids by sulfate reducing bacteria. The molecular mechanisms of bacterial resistance to copper are examined as well as extracellular electron transfer and bacterial metal oxide respiration. Furthermore, in this book enrichment, isolation, and physiology of magnetotactic bacteria are discussed.